Cost‐effectiveness of long‐acting insulin analogues vs intermediate/long‐acting human insulin for type 1 diabetes: A population‐based cohort followed over 10 years. Issue 5 (23rd January 2020) - Lee, Tsung‐Ying; Kuo, Shihchen; Yang, Chen‐Yi; Ou, Huang‐Tz
Abstract : Aims: This study assessed the cost‐effectiveness of long‐acting insulin analogues (LAIAs) vs intermediate/long‐acting human insulin (ILAHI) for patients with type 1 diabetes (T1D) in real‐world clinical practice. Methods: Individual‐level analyses were conducted within a longitudinal population‐based cohort of 540 propensity score‐matched T1D patients (LAIAs, n = 270; ILAHI, n = 270) with over 10 years of follow‐up using Taiwan's National Health Insurance Research Database, 2004–2013, from third‐party payer and healthcare sector perspectives. The study outcomes included the number needed to treat (NNT) to prevent one case of clinical events (eg, hypoglycaemia, diabetes‐related complications), medical costs, and cost per case of events prevented. Cost estimates are presented in 2013 British pounds (GBP, £). Results: The NNTs using LAIAs vs ILAHI to avoid one case of hypoglycaemia requiring medical assistance, outpatient hypoglycaemia and any diabetes‐related complications were 12, 9 and 10 for mean follow‐up periods of 5.84, 6.02 and 3.62 years, respectively. From third‐party payer and healthcare sector perspectives, using LAIAs instead of ILAHI saved GBP6924‐GBP7116 per case of hypoglycaemia requiring medical assistance prevented, GBP5346‐GBP5508 per case of outpatient hypoglycaemia prevented, and GBP3570‐GBP3680 per case of any diabetes‐related complications prevented. Sensitivity analyses considering sampling uncertainty showed that using LAIAs over ILAHI yields at least a 76% probability of cost‐saving for avoiding one case of hypoglycaemia requiring medical assistance, outpatient hypoglycaemia or any diabetes‐related complications. Conclusions: This real‐world evidence reveals that compared with ILAHI, the greater pharmaceutical costs associated with LAIAs for patients with T1D could be substantially offset by savings from averted hypoglycaemia or diabetes‐related complications.